2019
DOI: 10.1177/1359105319847261
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the scientific rigour of randomized controlled trials on the effectiveness of cognitive behavioural therapy and graded exercise therapy for patients with myalgic encephalomyelitis/chronic fatigue syndrome: A systematic review

Abstract: Cognitive behavioural therapy and graded exercise therapy have been promoted as effective treatments for patients with myalgic encephalomyelitis/chronic fatigue syndrome. However, criticism on the scientific rigour of these studies has been raised. This review assessed the methodological quality of studies on the effectiveness of cognitive behavioural therapy and graded exercise therapy. The methodological quality of the 18 included studies was found to be relatively low, as bias was prominently found, affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The PACE trial was one of 16 trials in a systematic review by Ahmed, Mewes and Vrijhoef (2020) who assessed the methodological quality of studies on the effectiveness of CBT and GET for PwME/CFS [172]. Ahmed et al reported that the methodological quality of the included studies was generally relatively low, with prominent biases affecting the main outcome measures of the studies (fatigue, physical functioning and functional impairment/status).…”
Section: Disregard Of the Principles Of Sciencementioning
confidence: 99%
“…The PACE trial was one of 16 trials in a systematic review by Ahmed, Mewes and Vrijhoef (2020) who assessed the methodological quality of studies on the effectiveness of CBT and GET for PwME/CFS [172]. Ahmed et al reported that the methodological quality of the included studies was generally relatively low, with prominent biases affecting the main outcome measures of the studies (fatigue, physical functioning and functional impairment/status).…”
Section: Disregard Of the Principles Of Sciencementioning
confidence: 99%
“…Current research and clinical recommendations that acknowledge a biomedical base and the PEM phenomenon, however, recognize that there is currently no scientific evidence for effective treatment of ME/ CFS and explicitly discourage curative CBT and GET forms (10,(33)(34)(35)(36)(37). Instead, pacing strategies are considered to be the most effective approach to reduce the risk of PEM relapse and retain or improve physical functioning and quality of life (10, [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] However, medication is always associated with gastrointestinal adverse reactions and addiction, and its effectiveness is controversial. [9] It is currently believed that cognitive behavioural therapy and graded exercise therapy can improve fatigue symptoms and physical function in patients with CFS in the short term, [10] but there is little evidence of their longterm efficacy, and their impact on mental health cannot be discounted. [11,12] Studies have revealed that many traditional complementary and alternative therapies originating from China, such as acupuncture, [13] cupping [14] and Qigong, [15] can alleviate the fatigue symptoms of CFS.…”
Section: Introductionmentioning
confidence: 99%